Can microplots contribute to rural households’ food security? Evaluation of a gender sensitive land allocation program in West Bengal, India. - Santos, F. (International Food Policy Research Institute, 2014)
Landesa, a nongovernmental organization focused on land legislation and programming among poor populations, supports government land allocation and regularization programs in India. This study is based on Nijo Griha, Nijo Bhumi (“My Home, My Land” or NGNB), a program by the government of West Bengal, India that aims to reduce poverty by allocating microplots to landless agricultural laborers and assist with homestead development. NGNB works with local communities to purchase and allocate small plots of land, with titles issued jointly under the names of the husband and the wife. In addition, NGNB helps beneficiaries connect with other government agencies responsible for the provision of assistance with housing and basic inputs, capacity building in homestead food production, and investments in infrastructure. This study evaluated the NGNB program and is result of collaboration between Landesa and the Gender, Agriculture and Assets Project (GAAP). The project examined how land ownership and joint titling affect households’ tenure security and agricultural investments, as well aswomen’s involvement in food and agricultural decision-making—outcomes that when enhanced are expected to lead to increased household food production and long-¬term food security.